Immunosuppression, peripheral inflammation and invasive infection from endogenous gut microbiota activate retinal microglia in mouse models. (23rd September 2016) - Maneu, Victoria; Noailles, Agustina; Gómez‐Vicente, Violeta; Carpena, Nuria; Cuenca, Nicolás; Gil, M Luisa; Gozalbo, Daniel
ABSTRACT: Although its actual role in the progression of degenerative processes is not fully known, the persistent activated state of retinal microglia and the concurrent secretion of inflammatory mediators may contribute to neuronal death and permanent vision loss. Our objective was to determine whether non‐ocular conditions (immunosuppression and peripheral inflammation) could lead to activation of retinal microglia. Mouse models of immunosuppression induced by cyclophosphamide and/or peripheral inflammation by chemically induced sublethal colitis in C57BL/6J mice were used. Retinal microglia morphology, spatial distribution and complexity, as well as MHCII and CD11b expression levels were determined by flow cytometry and confocal immunofluorescence analysis with anti‐CD11b, anti‐IBA1 and anti‐MHCIIRT1B antibodies. Retinas of mice with double treatment showed changes in microglial morphology, spatial distribution and expression levels of CD11b and MHCII. These effects were higher than those observed with any treatment separately. In addition, we also observed in these mice: (i) translocation of endogenous bacteria from gut to liver, and (ii) upregulation of TLR2 expression in retinal microglia. Using a mouse model of immunosuppression and gut colonization by Candida albicans, translocation of fungal cells was confirmed to occur in wild type and, to a higher extent, in TLR2 KO mice, which are more susceptible to fungal invasion; interestingly microglial changes were also higher in TLR2 KO mice. Hence, non‐ocular injuries (immunosuppression, peripheral inflammation and invasive infection from endogenous gut microbiota) can activate retinal microglia and therefore could affect the progression of neurodegenerative disorders and should be taken into account to improve therapeutic options.